Synthesis and SAR of a series of mGlu7 NAMs based on an ethyl-8-methoxy-4-(4-phenylpiperazin-1-yl)quinoline carboxylate core. Issue 22 (15th November 2020) - Kalbfleisch, Jacob J.; Reed, Carson W.; Park, Charlotte; Spearing, Paul K.; Quitalig, Marc C.; Jenkins, Matthew T.; Rodriguez, Alice L.; Blobaum, Anna L.; Conn, P. Jeffrey; Niswender, Colleen M.; Lindsley, Craig W.
Graphical abstract: Highlights: Discovery of a novel mGlu7 NAM chemotype. First NAM based on a terphenyl scaffold, similar to PPI α-helical mimetics. Novel piperazine bioisosteres identified. Abstract: A High-Throughput Screening (HTS) campaign identified a fundamentally new mGlu7 NAM chemotype, based on an ethyl-8-methoxy-4-(4-phenylpiperazin-1-yl)quinolone carboxylate core. The initial hit, VU0226390, was a potent mGlu7 NAM (IC50  = 647 nM, 6% L-AP4 min) with selectivity versus the other group III mGlu receptors (>30 μM vs. mGlu4 and mGlu8 ). A multi-dimensional optimization effort surveyed all regions of this new chemotype, and found very steep SAR, reminiscent of allosteric modulators, and unexpected piperazine mimetics (whereas classical bioisosteres failed). While mGlu7 NAM potency could be improved (IC50 s ~ 350 nM), the necessity of the ethyl ester moiety and poor physiochemical and DMPK properties precluded optimization towards in vivo tool compounds or clinical candidates. Still, this hit-to-lead campaign afforded key medicinal chemistry insights and new opportunities.